74 LAPAROSCOPIC MANAGEMENT OF A PULSION EPIPHRENIC OESOPHAGEAL DIVERTICULUM SECONDARY TO ACHALASIA. (17th September 2021) - Tan, Jeremy; Yeung, Baldwin; Ong, Lester; Toh, Bin Chet; Wong, Wai Keong; Lim, Chin Hong
Abstract:  : This is a video submission of a laparoscopic resection of an epiphrenic oesophageal pulsion diverticulum secondary to achalasia. A Heller's cardiomyotomy is also performed together with a Toupet fundoplication. Methods: The patient is a 40 year old woman with a 12 month history of worsening dysphagia, reflux symptoms, as well as occasional regurgitation of food, worse at night. Barium swallow showed a distal oesophageal diverticulum and oesophageal manometry confirmed type 1 achalasia. Upper GI endoscopy showed no other intra-luminal findings. Results: The patient underwent a laparoscopic resection of the diverticulum, together with a Heller's cardiomyotomy and Toupet fundoplication. There were no post-operative complications. She remains well and asymptomatic at 9 month follow-up. Conclusion: Pulsion diverticula secondary to achalasia are a known but rare entity. A few variations exist on how to manage this condition surgically, especially with respect to the type of fundoplication. We present our preferred technique for dealing with this condition. Video: https://www.dropbox.com/s/dg4edkamykugupn/Oesophagealdivert.mp4?dl=0